2018
DOI: 10.1016/j.ultsonch.2018.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-enhanced Ag-catalyzed decarboxylative coupling between α-keto acids and disulfides for the synthesis of thioesters

Abstract: Herein, we described the ultrasound-assisted synthesis of thioesters via the Ag-catalyzed radical oxidative decarboxylation of α-keto acids, in the presence of disulfides. This protocol takes advantage of the sonication to prepare the title compounds in moderate to very good yields, in only 20 min of reaction. The positive effect of ultrasonic irradiation is attributed to both, the high mass transfer efficiency and to the induced radical formation in the reaction medium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 62 publications
0
8
0
2
Order By: Relevance
“…Wang found that K 2 S 2 O 8 alone could promote this decarboxylation coupling with aliphatic and aromatic thiols under TM‐free conditions. Ag‐catalyzed decarboxylative thiolation with disulfides was found to proceed within 20 minutes under microwave irradiation [296] . In these reactions, acyl radicals seem to be the key intermediates.…”
Section: Decarboxylative C−chalcogen Bond Formationmentioning
confidence: 99%
“…Wang found that K 2 S 2 O 8 alone could promote this decarboxylation coupling with aliphatic and aromatic thiols under TM‐free conditions. Ag‐catalyzed decarboxylative thiolation with disulfides was found to proceed within 20 minutes under microwave irradiation [296] . In these reactions, acyl radicals seem to be the key intermediates.…”
Section: Decarboxylative C−chalcogen Bond Formationmentioning
confidence: 99%
“…Thus, based on the above observations and on previous reports involving electrophilic cyclization reactions, [70][71][72] the reactivity of Oxone ® [40,43,81] and reactions under ultrasonic irradiation, [77][78][79][80][81] a plausible mechanism for the formation of chalcogenophenes 7-9 from 1-3 is presented in Scheme 4.…”
Section: Resultsmentioning
confidence: 56%
“…When the reaction mixture was refluxed for 8 h, the expected product 7 a was isolated in 77 % yield. Then, encouraged by recent positive results described by our research group, [77][78][79][80][81] and interested in reducing the reaction time, the mixture was sonicated at 60 % of amplitude for 60 min, using an ultrasonic probe, obtaining the desired product 7 a in 78 % yield (Table 1, entry 1). Considering this yield as satisfactory, the influence of the solvent on the performance of the cyclization was investigated ( Table 1, entries 2-12).…”
Section: Resultsmentioning
confidence: 99%
“…More recently, Lenardão et al. described the US‐assisted synthesis of thioesters 91 via the Ag‐catalyzed radical oxidative decarboxylation of α‐keto acids 46 , in the presence of disulfides 63 . Thiol esters are involved in the biosynthesis of several natural polyketide antibiotics, such as penicillin and erythromycin, and many other applications in medicinal and organic chemistry .…”
Section: Synthesis Of Organochalcogen Compoundsmentioning
confidence: 99%